Directive Speech Acts in the Children's Novel "The Little Prince" by Antoine de Saint-Exupéry in Searle's Pragmatic Theory/ Al-Af’âl al-Kalâmiyah at-Taujîhiyah fi Riwâyah al-Athfâl “al-Amîr as-Shagîr li Antoine de -Exupéry fi Nadzariyah at-Tadâuliyah li Searle - Endah, Sofie Yopita Nur; Djamaluddin, Burhan (Al-Manar, 2024)
The novel "The Little Prince" by Antoine de Saint-Exupéry, a French writer, published in 1943, is considered one of the works of French children's literature, which has been translated into 300 languages other than French and has been distributed in 140 million copies. to date. Some people consider the novel "The Little Prince" to be one of the unforgettable masterpieces of world literature. In contrast to children's literature in general, Antoine de Saint-Exupéry's work in "The Little Prince" is not only aimed specifically at children, but also at adults who have forgotten their childhood experiences, making it difficult for them to understand the world of children's thoughts and feelings. Based on the reasons above, researchers are interested in studying children's literature The Little Prince in terms of directive illocutionary speech acts and their functions. Therefore, the aims of this research are 1) to find out what types of directive speech acts are in the children's novel The Little Prince by Antoine de Saint-Exupéry in Searle's Pragmatic Theory and 2) to find out the function of directive speech acts in the children's novel The Little Prince Antoine de Saint-Exupéry's work in Searle's Theory of Pragmatics. The results of this research, the researcher found 1) 2 forms of directive illocutionary speech acts found in the novel The Little Prince, namely direct speech acts and indirect speech acts, with details of 37 direct directive speech acts and 5 indirect directive speech acts; and 2) 5 functions of directive illocutionary speech acts contained in the novel The Little Prince, namely the functions of requesting, ordering, suggesting, prohibiting, and advising with details: function of requesting 14 utterances, function of commanding 15 utterances, function of suggesting 4 utterances, function of prohibiting 8 utterances , and the function of advising 11 utterances. Keywords: speech act, directive, searle, the little prince